Demystifying the Morphosyntactic Features of the Tagalog and English Languages: A Contrastive Analysis - Pedro P. Raymunde Jr (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study was conducted to analyze the morphological, syntactical, and morpho syntactical features of the Tagalog and English languages. This study employed a qualitative contrastive analysis research design. According to the findings, the two languages are made up of distinct morphological components: grammatical inflection is comprised of inherent inflections, pronoun and adjective inflections, and declensions; derivational affixation is comprised of verb conjugations; and grammatical markers are comprised of bound morphemes. When it comes to the syntactic patterns, Tagalog adheres to the predicate-initial pattern, also known as the V-S-O syntactic pattern, whereas English adheres to the S-V-O pattern. In contrast, in terms of morphosyntactic feature, the subject does not have a direct effect on the verb in Tagalog, whereas in English, the subject has a significant impact on the verb. Constructions using the active and passive voices are also different between the two.